Fabrication of a prototype mini bucket excavator - Farid Basheer, Farhan Dani (2025)
Agriculture is an activity practiced all over the world and from the starting of human civilization. Farming allows people to produce their own food supplies and some practice it at a larger scale for the purpose of selling it to others[4]. Nonetheless, some have intentions of farming crops on their own land and for their own needs only. As of these days, farming crops could have some complications as there are factors that restrict individuals from doing so[5][6]. For instance, time, available land, physical capability, affordability, and knowledge. By the invention of the Mini Bucket Excavator, it could eliminate some of the factors such as time, physical capability and affordability [7]. With this, agriculture around the world could be practiced individually and potentially lead to many benefits towards the individual, community and possibly to the world [8].